A Case Report on Integrated Management of Hematological Abnormalities like Thrombocytosis and Leukocytosis in Sickle Cell Crisis Patient - Desai, Atul; Desai, Kavita; Desai, Hemshree; Desai, Rutvij; Desai, Chirag; Purohit, Pinky (Indian Journal of Pharmacy Practice)
An Indian tribal population amongst dense forest area mainly suffers from sickle cell anaemia for a long. Considering the pathogenesis and geographical limitations only symptomatic management is available as there is no cure. Diagnosis of vaso-occlusive crisis or existing complication is a critical factor in sickle cell anaemia. Increased platelets, white blood cells, and clinical manifestations demand more attention in sickle cell patients. In the current case study, a patient was presented to the site for daycare management in minimal consciousness condition with SpO2 96% complains of left hip pain and unable to walk, joint pain, pallor, backache, and general weakness. The clinical evaluation thrombocytosis, leukocytosis, and x-ray suggested developed avascular necrosis of the hip. Considering his condition patient was started on an integrated treatment approach with T-AYU-HM Premium 300mg tablet. Regular monitoring of condition and strict adherence to treatment has lessened the financial and logistical burden of prolonged hospital stays, blood transfusion needs, and vaso-occlusive crisis sequelae. A key observation in this case study is a remarkable improvement in thrombocytosis, leukocytosis, and walking impairment in patient due to avascular necrosis. Looking at the improvement in the clinical conditions to proceed with utilising the information for better healthcare, a patient had consented for the same. The prognostic significance of platelet and white blood cells is suggestive of disease severity and progression in sickle cell anaemia patients. During the treatment, no untoward effect was reported or observed. This integrated treatment approach might become helpful in managing such kind of clinical complications in sickle cell anaemia.
Keywords: Thrombocytosis; Leukocytosis; Vaso-occlusive crisis; Avascular necrosis; Sickle cell disease